Sistem Pendukung Keputusan Pemilihan Siswa Terbaik Berbasis Web Menggunakan Metode Analytical Hierarchy Process - Anggrita Loda; Andreas Ariyanto Rangga; Diana Reby Sabawaly (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Students who excel must receive guidance on the development of each student's individual potential in order to produce superior and quality students. To complete this task, student achievement is taken into account. The Analytical Hierarchy Process (AHP) approach is one method that can be utilized in decision support systems. can do weighting to determine selection criteria and alternatives, starting from the definition of the problem. The purpose of evaluation or weighting in a decision support system, such as that carried out using the Analytic Hierarchy Process (AHP) approach, is to assess and compare the value or characteristics of each alternative based on predetermined criteria. This process allows us to understand how important each criterion is in achieving the main goal, so that the decisions taken are more structured and objective. Based on the method used, the system provides valid and accurate findings. The final result of determining the priority weight of alternatives based on ranking